In Vitro Anti-Cancer Alkaloid and Flavonoid Extracted from the Erythrina variegata (Leguminoseae) Plant - Herlina, Tati; Supratman, Unang; Subarnas, Anas; Sutardjo, Supriyatna; Amien, Suseno; Hayashi, Hideo (Indonesian Journal of Cancer Chemoprevention, 2011)
Erythrina plants, locally known as âdadap ayamâ, are higher plant species and have beenÂ used as a folk medicine for treatment of cancer. To prove the effectiveness of the leaves andÂ stem bark of E. variegata as an anti-cancer agent, the assay in this research was focused on inÂ vitro Â test Â towards Â breast Â cancer Â cell Â T47D. Â In Â the course Â of Â our Â continuing Â search Â for novelÂ anti-cancer agent from Erythrina plants, the methanol extract of the leaves and stem bark of Â E.Â variegata Â showed Â significant Â anti-cancer Â activity Â against Â breast Â cancer Â cell Â T47D Â in Â vitro Â usingÂ the Sulphorhodamine B (SRB) assay. By using the anti-cancer activity to follow the separations,Â the methanol extract was separated by combination of column chromatography. The chemicalÂ structure Â of Â an Â anti-cancer Â compounds Â were Â determined Â on Â the Â basis Â of Â spectroscopicÂ evidence Â and Â comparison Â with Â the Â previously Â reported Â and Â identified Â as Â an Â erythrina Â alkaloidÂ (1) Â and Â isoflavonoid Â (2). Â Compounds Â (1-2) Â showed Â anti-cancer Â activity Â against Â breast Â cancerÂ cell Â T47D Â used Â with Â IC50 Â of Â  Â 1.0 Â and Â 3.3 Â Âµg/mL, Â respectively. Â This Â results Â strongly Â suggestedÂ that E. variegata is promising sources for anti-cancer agents.Keywords: Anti-cancer, Erythrina variegata, Leguminoseae